The Depiction of Antibiotic Use without Presciption and Community Attitudes Towards Drugstores that Refused to Sell Antibiotic without Prescription - M Rifqi Rokhman; Satibi Satibi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Antibiotic resistance causes reduced therapeutic effectiveness. Understanding of people's behavior plays an important role in countering antibiotic resistance especially by preventing irrational use of antibiotics. The purpose of the study was to depict the experience of respondents in using antibiotics without prescription and the relationship of characteristics of respondents with unwillingness to remain a customer at a pharmacy that had refused to provide antibiotics without a prescription. The study design applied cross-sectional using a questionnaire, and sampling was done by purposive sampling. Respondents were people who used antibiotics without a doctor's prescription. The survey was conducted in Yogyakarta in September-October 2018. The data were analyzed descriptively and used multivariate logistic regression. As many as 44.2% of the total 670 respondents used antibiotics the last time more than a year ago; 69.5% received information about antibiotics from previous treatments; 93.4% received antibiotics from pharmacies, and 69.2% stated that the most used antibiotic was amoxicillin. More than half (62.2%) of respondents were still willing to become customers at a pharmacy that had refused to provide antibiotics without a prescription. Respondents with high school education or lower as the latest education degree (OR = 1.513; 95% CI 1.017-2.252); from family income below the regional minimum wage (OR = 1.858; 95% CI 1.302-2.651), and from Sleman Regency (OR = 1.457; 95% CI 1.016-2.089) became a predictor of the unwillingness of respondents to become customers at a pharmacy who had refused to provide antibiotics without a prescription. Supervision of antibiotic (especially amoxicillin) in pharmacies and education to the community needs to be used as part of a strategy against irrational use of antibiotics. In addition, education needs to be given to pharmacists to reduce fears of decreased in the number of their customers because they refuse to deliver antibiotics without a prescription.